Enantioselective Construction of Spiro[chroman‐thiazolones]: Bifunctional Phosphonium Salt‐Catalyzed [2+4] Annulation between 5‐Alkenyl Thiazolones and ortho‐Hydroxyphenyl‐Substituted para‐Quinone Methides. Issue 5 (18th December 2019) - Tan, Jian‐Ping; Zhang, Hongkui; Jiang, Zhiyu; Chen, Yuan; Ren, Xiaoyu; Jiang, Chunhui; Wang, Tianli
Abstract: The enantioselective formal [2+4] annulation of 5‐alkenyl thiazolones with hydroxyl‐substituted para ‐quinone methides was disclosed by dipeptide‐based phosphonium salt catalysts. A wide range of functionalized spiro‐chroman‐thiazolone molecules bearing three contiguous 3° and/or 4° stereocenters were readily constructed in high yields with excellent stereoselectivities (>20:1 dr and up to >99.9% ee) under low catalyst loading and mild reaction conditions. The practicality and utility of this protocol were demonstrated by the scaled‐up preparation and elaborations of product. Abstract :